PERAN PEKTIN DAN SUKROSA PADA SELAI UBI JALAR UNGU (The Role of Pectin And Sucrose On Purple Sweet Potato Jam) - Yulistyani, Ratna; Murtiningsih, Ir; Mahmud, Munifa (UPN VETERAN JAWA TIMUR, 2011)
Purple sweet potato (Ipomoea Batatas L. Poir) is vines that contain lots of anthocyanins (11, 051 mg/100 gr) and fiber (3%) is highly beneficial to human health (Suprapta, 2006). Jam is a made form count, rest of sieve or mill fruit cooked with sugar to mixed thick (Susanto,1993).The process of jams faced purple sweet potato is not formation gels. This study aims to determine the effect of the addition of pectin and sucrose on the quality of purple sweet potato jam. This research using a Complete Randomized Design factorial patterns with two factors and three replications. The first factor : addition of pectin (0,5%, 1% , 1,5%) and the second factor : sucrose (55%, 60%,65%).The best results was pectin (1%) and sucrose (65%) resulting purple sweet potato jam with content of anthocyanins (9.935%), water 54.85%, water activity 0.86, crude fiber 51.62%, total of dissolved solids 60.94%, pH 3.4 and a smear of jam 12.2 %. The color of favorite values (111.5), taste (142), flavor (129) and texture (122.5).Key words : purple sweet potato, jam, pectin, sucrose